Level of physical activity participation and work performance among employees in UiTM Seremban / Nursyamimi Supardi - Supardi, Nursyamimi (2016)
This study addressed four main purposes, which are; ( 1) to identify the level of physical activity participation among employee; (2) to examine the employee work performance; (3) to compare the physical activity participation between genders; and to identify the relationship between physical activity participation and work performance among employee. This study utilized quantitative design. The 27 items from International Physical Activity Questionnaire (IPAQ) and 18 items from the Individual Work Performance Questionnaire (IWPQ) was administered among (N=373) employee in Universiti Teknologi MARA (UiTM) Seremban campus and divided into two, academic staff and non-academic staff. The results showed the highest percentage for high level of physical activity 119(61 %) and the highest mean of work performance is task performance(i = 4.101). The results of Independent sample T-test were indicated that there is no significant difference (t = 1.503, p = .135) recorded between male and female score of physical activity participation. Besides that, the result of Correlation analyses indicated were r = .076 (low correlation) and p value <0.05 (not significant). The researcher concludes that analyses suggested that there is no relationship between variables.